Analisis Tata Ruang Pada Kawasan Bergambut Di Kecamatan Dolok Sanggul Kabupaten Humbang Hasundutan - Edwar Darmansyah Pohan; Erwin Nyak; Achmad Siddik Thoha (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Peatland conversion has become a serious issue in recent years. The dynamic between peatland protection and limited space for urban development is a strategic issue in spatial planning. This research aims to evaluate the spatial pattern planning of peatland areas in the 2018 Regional Spatial Plan of Humbang Hasundutan District. The focus of this research is a peatland area of 666.77 hectares. The method used in this research is descriptive qualitative with a spatial data exploration approach using ArGIS 10.8 application. The results show that the spatial pattern plan of peatland in 2018 has a mismatch in spatial use, non-peatland reaches 357.06 hectares (53.55%), most of which is used as fields/crops (39.10%) and settlements (3.04%). The extent of land rights reaches 118.47 hectares (17.77%), while land without land rights is dominated by swamp land use (32.96 hectares or 41.51%). Cultivated land has the largest share (62.72%) as a potential cultivation function. Improvements to the spatial pattern plan for peatlands have decreased in area by -295.84 hectares (-44.37%), which needs to be considered in the future revision of the Humbang Hasundutan District Spatial Plan, including the regulation of general zoning provisions.